Collaborative gvernance for a better education in Colombia (2016)
The greatest challenges of the 21st century demand greater coordination and cooperation between public entities, private sector and communities, which should seize the new opportunities that technological innovations can bring for sustainable development. In Colombia the public policy, "Plan Vive Digital" allowed the reduction of digital divide through connection of remote areas of the country by broadband, using a collaborative governance approach. This enabled the increase of coverage of education, but at the same time it showed new challenges for the quality of education.